Pengaruh Pengungkapan Corporate SocialResponsibility Terhadap Nilai Perusahaan denganKepemilikan Manajerial sebagai VariabelPemoderasi(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa EfekIndonesia Periode 2010-2014) - Wulandari, Fitria Ika, Drs. Muhammad Abdul Aris, M.Si (2016)
This study aimed to analyze the effect of disclosure of corporate social responsibility (CSR) and managerial ownership to firm value. The firm value is measured by Tobin's Q. While managerial ownership is measured by the percentage of shares held by managers, boards of directors and commissioners. Measurement of corporate social responsibility (CSR) is based on global reporting intiatives disclosure index (GRI) in 2013. The population of this research is all manufacturing companies listed in indonesia stock exchange 2010-2014. Sample was taken by purposive sampling and found 25 companies, with 5 years of observation. So the total sample studied was 125. The data analysis was performed with the classical assumption and hypothesis testing with multiple linear regression method. The results show that the disclosure of corporate social responsibility (CSR), managerial ownership and incorporation of corporate social responsibility (CSR) and managerial ownership significantly influence toward the value of the company.